2018
DOI: 10.1002/adem.201701065
|View full text |Cite
|
Sign up to set email alerts
|

The Solid Flame Phenomenon: A Novel Perspective

Abstract: In this paper, the authors overview previous publications and present novel results related to self-sustained solid-state reactions: the solid flame. Due to recent advances in the fabrication of nano-structured reactive media, this phenomenon, which is first reported fifty years ago, has found a new perspective for a wide variety of exothermic systems. These fundamental findings permit novel routes for synthesis of advanced engineering materials with controlled microstructure, as well as for design of high-ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
(60 reference statements)
0
15
0
Order By: Relevance
“…The goal of the second preparation stage is to introduce nitrogen into the system in the form of metal nitrides, as well as nitrogen solid solutions. This task was accomplished by using energy-saving combustion synthesis method 31 . Supplementary Table S-II demonstrates that the reactions between considered metals and nitrogen are highly exothermic with adiabatic combustion temperature well above 3000 K. The reaction between the metal composite particles and nitrogen was initiated locally by hot tungsten wire, followed by the rapid combustion front propagation along with the media.…”
Section: Resultsmentioning
confidence: 99%
“…The goal of the second preparation stage is to introduce nitrogen into the system in the form of metal nitrides, as well as nitrogen solid solutions. This task was accomplished by using energy-saving combustion synthesis method 31 . Supplementary Table S-II demonstrates that the reactions between considered metals and nitrogen are highly exothermic with adiabatic combustion temperature well above 3000 K. The reaction between the metal composite particles and nitrogen was initiated locally by hot tungsten wire, followed by the rapid combustion front propagation along with the media.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the two-stage formation of Al 3 Ni proceeds at heating rates above 100 K/s as well as under runaway conditions. For 1000 K/s, the solid-state reaction turns into a "solid flame" 34,35 which is reported for the first time for nanoscale Al/ Ni multilayers.…”
mentioning
confidence: 76%
“…Interestingly, it was recently experimentally verified [34][35][36] that runaway reactions may also proceed in the solid state, sometimes called as ideal solid flame. The melting points of the reactants and products have to be higher than the adiabatic reaction temperature.…”
mentioning
confidence: 99%
“…The Nickel and Aluminum binary system in different forms such as particles, powder, flakes, nanorods, and foils, were under intensive investigation since the end of the 20th century [1][2][3][4][5][6][7][8][9][10][11][12][13]. Fast and steady reaction and releasing a huge amount of energy on a very short time scale are the main beneficial aspects, applied in different fields of science and engineering.…”
Section: Introductionmentioning
confidence: 99%